MUNICIPAL SOLID WASTE MANAGEMENT IN BANI WALID CITY, LIBYA: PRACTICES AND CHALLENGES - ABDELNASER, Omran; ALSADEY, Salahalddin; GAVRILESCU, Maria (Journal of Environmental Management and Tourism; Vol 2 No 2 (2011): JEMT Volume II Issue 2(4) Winter 2011, 2011)
Rapid expansion of industry, urbanization and increasing population, especially in large cities like Bani Walid, has dramatically increased the amount of municipal solid waste (MSW) generated in Libya. However, issues related to environmentally sound municipal solid waste management – including waste reduction and disposal – have not been addressed adequately. Open dumping is currently the most popular form of waste disposal for about 1,200,000 of tons of waste annually. In recent years, most developing countries have started to improve their solid waste management practices. Although a huge portion of Bani Walid’s budget goes for municipal solid waste management (MSWM), poor collection and inadequate transportation of wastes continue and result in the accumulation of waste throughout the city of Bani Walid. This paper presents an overview of current MSWM practices in Bani Walid city (Libya) and suggests solutions to some of the major problems, since at this time no treatment is applied to the waste, which is dumped after collection. In this context, when suitable facilities (equipment and infrastructure) are missing, government and authorities in Bani Walid should examine the possibilities of involving the private sector to ensure efficient management of solid wastes in its areas